Analisis Pengawasan Penyelenggaraan Financial Technologi Oleh Otoritas Jasa Keuangan Pasca Putusan MA Nomor 1206/K/PDT/2024 - shafira, belgis; Miftah, Farrah; Rahayu, Dewi (Jimly School of Law and Government, 2024)
Digital financial innovation provides easy access to the financial industry. Convenience can be felt in the process of transferring funds, non-cash payments, to funding services through applications or websites. This is called the P2P lending service which is under the supervision of the OJK. However, this supervision has not been implemented optimally, as evidenced by the large number of illegal P2P lending service providers in Indonesia, misuse of personal data by P2P lending providers, collection processes that are not in accordance with regulations, and complaint processes that do not receive feedback. This concern was expressed in a citizen lawsuit and was agreed to by the Supreme Court in the Cassation Decision Number 1206/K/PDT/2024. Therefore, it is necessary to study further in depth and comprehensively regarding the urgency of supervising the implementation of P2P lending in Indonesia and how to protect P2P lending consumers after the Supreme Court Decision Number 1206/K/PDT/2024. By using a normative legal research method through a legislative approach and a conceptual approach, it is hoped that it can provide answers to the formulation of the problem that is the focus of the research issue. The results of the analysis are OJK as mandated by Article 5 of the OJK Law states that the implementation of fintech is the authority of OJK in carrying out supervision. Supervision by OJK is needed in order to guarantee the rights and obligations of the parties and to be able to minimize the number of illegal P2P lending organizers in Indonesia. There is still overlapping legal protection for consumers as users of P2P lending service providers. So it is appropriate if OJK then issues the LPBBTI 2023-2028 roadmap as an effort to be able to enforce the legal protection process as in the Supreme Court Cassation Decision Number 1206 / K / PDT / 2024.